Delik Penghinaan dan Beberapa Aspeknya Studi Perbandingan Antara Indonesia dan Amerika - Lesmana, Tjipta (Pelita Harapan University, 2006)
Press freedom in Indonesia enjoys euphoria following the downfall of Soeharto regime in May 1998. Embarking libertarian theory Indonesia press is putting heavily its function as watchdog, monitoring and supervising all aspects of life in the nation, notably government activities. But the radical change in press life was generally viewed with high discontent among people. They regard the phenomenon as